Penegakan Hukum terhadap Pengelolaan Sumber Daya Air Tanpa Izin di Indonesia - Susi Sopiani; Suwari Akhmaddhian (Program Studi Ilmu Hukum, Universitas Kuningan, 2025)
Water resources are essential for human life and ecosystems on Earth. Water resource management in Indonesia is an increasingly pressing issue due to the increasing need for clean water and the increasingly apparent impacts of climate change. The purpose of this study is to determine the regulation and implementation of unlicensed water resource management in Indonesia. The research method used is a normative juridical research method with a case approach, which analyzes court decisions and the relevance of existing laws and regulations. The results conclude that legal regulations regarding unlicensed water resource management have been formulated comprehensively, one of which is regulated in Law Number 17 of 2019 concerning Water Resources. Its implementation indicates that these violations are caused by low public legal awareness and weak oversight by the authorities. The judge's decision to grant probation reflects an educational and restorative justice approach in the Indonesian legal system. In conclusion, to improve the effectiveness of legal implementation, more intensive socialization regarding water resource licensing and strengthened oversight by the government and law enforcement officials are needed. This is expected to build a legal culture that supports the legal and sustainable sustainability of water resources.